2019
DOI: 10.1016/j.jses.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes of reverse total shoulder arthroplasty: a comparative risk factor analysis of improved versus unimproved cases

Abstract: BackgroundThe purpose of this study was to compare characteristics of patients who reported to be subjectively unimproved vs. improved after reverse total shoulder arthroplasty.MethodsData were derived from a prospective registry of patients who underwent reverse total shoulder arthroplasty with a minimum 2-year follow-up. Patients were asked to rate their subjective satisfaction and then divided into those who were unchanged or worse (unimproved group [UG]) vs. better or much better (improved group [IG]). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The improved group had a mean increase in shoulder forward elevation of 55.5° and abduction of 47.4° compared with the unimproved group who had an increase in forward elevation of 26.0° and abduction of 20.6°. 7 Our population demonstrated a global increase in shoulder ROM postoperatively, which was not influenced by thoracic kyphosis. Comparatively, patients with kyphosis <25°, between 25 and 45°, and >45° had an increase in shoulder forward elevation of 47.5°, 44.5°, and 46.4°, respectively.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The improved group had a mean increase in shoulder forward elevation of 55.5° and abduction of 47.4° compared with the unimproved group who had an increase in forward elevation of 26.0° and abduction of 20.6°. 7 Our population demonstrated a global increase in shoulder ROM postoperatively, which was not influenced by thoracic kyphosis. Comparatively, patients with kyphosis <25°, between 25 and 45°, and >45° had an increase in shoulder forward elevation of 47.5°, 44.5°, and 46.4°, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…[1][2][3][4][5][6] Dissatisfaction rates after primary rTSA for degenerative conditions and rotator cuff pathology reach up to 9%. 7 Risk factors for patient dissatisfaction after rTSA include decreased preoperative shoulder range of motion (ROM), lower preoperative patient-reported outcome measures (PROM), history of previous shoulder surgery, history of coronary artery disease or diabetes, and tobacco use. [7][8][9][10] Although many of these risk factors are nonmodifiable, surgeons can incorporate known risk factors into preoperative counseling to manage patient expectations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a concern in the literature about identifying the factors that influence the final result of RSA. Parsons et al 8 found that approximately 9% of patients who underwent primary RSA were dissatisfied with the result and that these cases were usually related to comorbidities, such as coronary disease, diabetes, and previous shoulder surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the functional outcome, Parsons et al 8 looked for risk factors for failure after RSA. They found that patients with coronary heart disease, diabetes and previous joint surgery were more likely to have worse functional outcomes, although they were not correlated with the pre-operative expectations of these patients.…”
Section: Introductionmentioning
confidence: 99%